Can the BRICS Games replace the Olympics? - Shvetsov A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The purpose of thisworkis to study the results of the participation of Russianathletesin the VBRICSGames,aswell as to assess the contribution of thesecompetitions to theformation of an alternativemodel of internationalsportingevents. Methods and structure of the study.Toachieve this goal, an analysis of informationmaterialsrelated to Olympicissueswascarried out. Results and conclusions. The study found that in March 2022, Russian and Belarusian athletes were excluded from most international competitions on the recommendation of the IOC Executive Committee. The reason for this decision was a special military operation conducted by the Russian Federation on the territory of Ukraine. After two years of restrictions, Russia has demonstrated its ability to organize large-scale competitions by successfully hosting the V BRICS Games. This event can serve as a starting point for the development of a new international competition system independent of the IOC.